The durability of flexible eddy current array (FECA) sensors in harsh service environments - Yujian Song (Nature Portfolio, 2021)
Abstract Sensors for structural health monitoring (SHM) need to be permanently integrated on structures and withstand the harsh service environments, which has been a big challenge for the application of SHM in aircrafts. This paper focuses on the durability of flexible eddy current array (FECA) sensors in harsh service environments of aircrafts, including vibration environment and several typical exposed environments. First, a kind of FECA sensor is illustrated and its integration method is proposed. Moreover, in order to study the durability of the sensor in vibration environment, the modal analysis is performed by the finite element method. According to the simulation results, the durability experiment in vibration environment is carried out under the fourth order vibration mode, which makes the sensor suffer the harshest vibration loads. During the vibration experiment, output signals of the sensor keep stable and the sensor is well bonded to the structure, which shows the integrated sensor has high durability in vibration environment. Finally, the durability of integrated sensors is separately tested in three exposed environments, including salt fog corrosion environment, fluid immersion environment, as well as hygrothermal and ultraviolet-radiation environment. After these environmental exposure experiments, all sensors are well bonded to structures and can effectively monitor fatigue cracks, which shows great durability. Therefore, FECA sensors can survive in harsh service environments of aircrafts, which provides important support for the engineering applications of FECA sensors.